Do We Really Know How to Treat a Child with Bipolar Disorder or One with Severe Mood Dysregulation? Is There a Magic Bullet?. (1st December 2011) - Jairam, Rajeev; Prabhuswamy, Mukesh; Dullur, Pravin
Abstract : Background . Despite controversy, bipolar disorder (BD) is being increasingly diagnosed in under 18s. There is scant information regarding its treatment and uncertainty regarding the status of "severe mood dysregulation (SMD)" and how it overlaps with BD. This article collates available research on treatment of BD in under 18s and explores the status of SMD. Methods . Literature on treatment of BD in under 18s and on SMD were identified using major search engines; these were then collated and reviewed. Results . Some markers have been proposed to differentiate BD from disruptive behaviour disorders (DBD) in children. Pharmacotherapy restricted to short-term trials of mood-stabilizers and atypical-antipsychotics show mixed results. Data on maintenance treatment and non-pharmacological interventions are scant. It is unclear whether SMD is an independent disorder or an early manifestation of another disorder. Conclusions . Valproate, lithium, risperidone, olanzapine, aripiprazole and quetiapine remain first line treatments for acute episodes in the under 18s with BD. Their efficacy in maintenance treatment remains unclear. There is no validated treatment for SMD. It is likely that some children who are currently diagnosed with BD and DBD and possibly most children currently diagnosed with SMD will be subsumed under the proposed category in the DSM V of disruptive mood dysregulation disorder with dysphoria.